Experimental Examination of an Axial Compressor as a Basis for an Active Stall Avoidance System - Richard Schulze; Dietmar K. Hennecke; Thuyen Le; Manfred Glesner (International Journal of Rotating Machinery)
A single-stage subsonic compressor was examined with respect to compressor instabilities. During the inception of rotating stall, the transients of the pressure rise and mass flow were measured as well as their hysteresis. The development of the stall cell and the characteristics of the unstable operating range were determined.